Supporting victims of crime in England and Wales: Local commissioning meeting local needs?. Issue 2 (May 2018) - Hall, Matthew
This paper will focus on how support services for victims of crime have developed in England and Wales since the advent of the 2010 coalition government of the United Kingdom. In particular, the discussion will centre around the development of a framework of locally commissioned victim service providers effectively replacing a previous model of central funding aimed largely at a single national organisation, the charity Victim Support. Both the conception and the implementation of this strategy by government and local actors – notably regional Police and Crime Commissioners – will be critically assessed in order to test government claims concerning the utility of such a system for victims of crime themselves. In so doing, it will be argued that in practice it has been difficult to discern how specific local needs can be identified or catered for under these new arrangements. The paper will also demonstrate a great deal of variance in the ways Police and Crime Commissioners have approached these tasks. Ultimately, it will be suggested that what is often touted as a general sea-change in favour of crime victims as a whole may in fact be grounded more in a neo- liberal, market ideology. Local commissioning also, it is argued, represents a continuing prioritisation of certain victims of crime for attention by central government whilst keeping the support needs of the vast majority of 'more typical' victims of crime at arm's length.